Filogeografia de Bubulcus ibis (Linnaeus, 1758) na África e o processo de colonização do continente americano por essa espécie - Castillo, Carlos Congrains (Universidade Federal de São Carlos, 2013)
The cattle egret (Bubulcus ibis [Ardeidae]) was first reported in the New World in the late nineteenth century and has been found scattered throughout the Americas since the 1950s. The aim of the present study was to analyze the distribution of genetic diversity in African and Brazilian populations of the cattle egret to understand the process of colonization of the non-native area in the Brazil. Genetic variation in the mitochondrial DNA (mtDNA) Control Region (CR) (n = 412 African and 177 Brazilian individuals), in ATPase 6 and 8 genes (n = 108 African and 49 Brazilian individuals) and in the intron 5 of the nuclear transforming growth factor beta-2 gene (n = 96 African and 50 Brazilian individuals) were evaluated. Genetic diversity across regions of Africa was similar, except for the lesser diversity found in South Africa. Neutrality tests, mismatch distributions and Bayesian skyline plots revealed demographic expansion in the overall African population, dated by the latter method as 15000 years before the present, occurred after the last glacial maximum. The findings were discussed hypothesizing that past climatic events have shaped the current distribution of genetic diversity. AMOVA and pairwise Fst tests revealed a lack of differentiation among nearly all African populations. The few cases of differentiation involved the South African and/or Nigerian populations. Brazilian populations exhibited no genetic structure or effective size deviations over time. Mitochondrial and nuclear DNA genetic variability demonstrated similar levels of genetic variation between the Brazilian and African populations, suggesting multiple introduction events. Based on historical and genetic data (differentiation levels and shared haplotypes), we propose a likely migration route between both continents departing from West Africa, passing through oceanic islands and archipelagos, such as Cape Verde, and finally arriving in the Americas on the northern and/or southern coast of Brazil.
Keywords: Genética; Garça-vaqueira; Filogeografia; Demografia; Invasão biológica; Estrutura populacional; Bubulcus íbis; Bubulcus ibis; Phylogeography; Demographic history; Biological invasion; Population structure; CIENCIAS BIOLOGICAS::GENETICA